POTENSI USAHA DAN EFISIENSI EKONOMI RAKYAT DI KABUPATEN OGAN KOMERING ULU TIMUR - Zulkarnain Ishak; Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2009)
The objectives of the study are to analyze economic potential and efficiency on small scale economic or